Evaluation of Breast Cancer Incidence Trends in the Karaganda Region of Kazakhstan - Nurbek Igissinov; Asem Toguzbayeva; Zhansaya Telmanova; Aida Baibusunova; Almazhan Abdykalikova; Gulnur Igissinova; Zarina Bilyalova; Olzhas Akyshev; Serikbay Orazbayev; Zhanar Kozhakhmetova; Zhanerke Azhetova; Gaukhar Nurtazinova; et al. (Tehran University of Medical Sciences, 2022)
Background: The study conducted a component analysis of the dynamics of the incidence of breast cancer (BC) in Karaganda region. Methods: Primary data were for registered patients with BC (ICD 10-C50) in Kazakhstan, Karaganda region the period of 2009-2018. Evaluation of changes in BC incidence in the population of Karaganda was performed using component analysis according to the methodological recommendations. Results: Overall, 4,391 new cases of BC and 1,202 deaths were recorded. The incidence rate increased from 44.4 (2009) to 72.7 in 2018 and the overall growth was 28.37 per 100,000 population of female, including due to the age structure - ∑ΔA=3.13, due to the risk of acquiring illness - ∑ΔR=22.69 and their combined effect - ∑ΔRA=2.56. The component analysis revealed that the increase in the number of patients with BC was mainly due to the growth of the population (ΔP=+3.7%), changes in its age structure (ΔA=+10.3%) and changes associated with the risk of acquiring illness (ΔR=+75.0%). The mortality rate in the region changed from 18.6 (2009) to 10.9 (2018) and tended to decrease. Conclusion: The role of the influence of demographic factors and the risk of acquiring illness on the formation of the number of patients and the incidence of BC was evaluated. In this region, these indicators were the highest. The implementation of the results of this study is recommended in management of anticancer activities for BC.